2010
DOI: 10.1161/atvbaha.109.202309
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Induces Peroxisome Proliferator-Activated Receptor-γ Activation in Macrophages and Suppresses the Progression of Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: Objective-Nifedipine, an L-type calcium channel blocker, protects against the progression of atherosclerosis. We investigated the molecular basis of the antiatherosclerotic effect of nifedipine in macrophages and apolipoprotein E-deficient mice. Methods and Results-In macrophages, nifedipine increased peroxisome proliferator-activated receptor-␥ (PPAR␥) activity without increasing PPAR␥-binding activity. Amlodipine, another L-type calcium channel blocker, and 1,2-bis-(oaminophenoxy)-ethane-N,N,-NЈ,NЈ-tetraacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
3
40
0
1
Order By: Relevance
“…Ishii et al demonstrated that nifedipine activated PPARγ through the inactivation of ERK, leading to the suppression of MCP-1 and ABCA1 (ATP-binding cassette transporter, subfamily A, member 1) expression in macrophages. Nifedipine has also been reported to increase luciferase activity by full-length PPARγ but not by a PPARγ-GAL4 chimera, indicating that nifedipine is not a direct PPARγ ligand and may not increase intracellular natural PPARγ ligands, whereas nifedipine has an agonistic effect on PPARγ activity (13). Notably, amlodipine did not increase PPARγ activity, indicating that PPARγ activation is not a common effect of L-type calcium channel blockers.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Ishii et al demonstrated that nifedipine activated PPARγ through the inactivation of ERK, leading to the suppression of MCP-1 and ABCA1 (ATP-binding cassette transporter, subfamily A, member 1) expression in macrophages. Nifedipine has also been reported to increase luciferase activity by full-length PPARγ but not by a PPARγ-GAL4 chimera, indicating that nifedipine is not a direct PPARγ ligand and may not increase intracellular natural PPARγ ligands, whereas nifedipine has an agonistic effect on PPARγ activity (13). Notably, amlodipine did not increase PPARγ activity, indicating that PPARγ activation is not a common effect of L-type calcium channel blockers.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, amlodipine did not increase PPARγ activity, indicating that PPARγ activation is not a common effect of L-type calcium channel blockers. In addition, nifedipine was found to enhance the effects of other PPARγ agonists, pioglitazone and ciglitazone-induced PPARγ activation (13). Thus, the combination of nifedipine with thiazolidinediones may enhance the prevention of NAFLD or NASH in metabolic syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, these are used to treat a variety of diseases including hypertension, angina pectoris, certain forms of cardiac arrhythmias, congestive heart failure, and hypertrophic cardiomyopathy. 10,11 Because aneurysm formation is a chronic inflammatory process, and several studies have linked LTCC blockers to anti-inflammatory effects in vitro 12 and in vivo, 13 we hypothesized that DIL attenuates aneurysm formation and tested this aspect in the ATII-infusion model of ApoE −/− mice.…”
mentioning
confidence: 99%